Masyarakat Madani dan Hegemoni Media: Pembentukan Masyarakat Moderat di Era Digital - Kris Nandang (Journal of Religion and Social Transformation, 2023)
Mainstreaming religious moderation is a must in a pluralistic Indonesian society in the midst of the changing times. This article aims to analyze the succession of the development of a moderate society at the time of the Prophet Muhammad as a stepping stone for the internalization of today's moderation values. Given the rapid development of information and communication media, society is faced with the problem of healthy media from radicalization. By using the literature review method, the author seeks to find the values ​​of moderation instilled by the Prophet Muhammad and their relevance to the present. The results of this study show: that first, the model of civil society is a model of moderate society under the auspices of the moral and intellectual leadership of the Prophet Muhammad. Second, the formation of a moderate society is built holistically in public society and media society. Third, the mainstream of religious moderation in the media is an effort to build hegemony with intellectuals as the axis.